2016
DOI: 10.1080/02640414.2016.1192672
|View full text |Cite
|
Sign up to set email alerts
|

Kicking modality during erratic-dynamic and static condition effects the muscular co-activation of attacker

Abstract: The purpose of the study was to investigate the effect of different kicking modality, i.e., erratic-dynamic target (EDT) versus static target (ST) on the performance of the roundhouse kick in two groups of taekwondo athletes of different skill level. Three-dimensional analysis and surface electromyography (SEMG) analysis were performed on 12 (Group A: six sub-elite, Group B: six elite) athletes to investigate muscle co-activation pattern under two conditions, i.e., EDT versus ST. In the results, the muscle rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In addition, it is also consisted of skills and physical arts that is an active and dynamic (3) that involves multiple muscles. The activity of these muscles is associated with flexion, extension and rotation of various joints (4,5). Foot techniques in Karate include Mae-Geri, Mawashi-Geri, Ora Mawashi-Geriand Yoko-Geri.…”
Section: Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is also consisted of skills and physical arts that is an active and dynamic (3) that involves multiple muscles. The activity of these muscles is associated with flexion, extension and rotation of various joints (4,5). Foot techniques in Karate include Mae-Geri, Mawashi-Geri, Ora Mawashi-Geriand Yoko-Geri.…”
Section: Contextmentioning
confidence: 99%
“…It is recommended that the foot rotation can be performed after the implementation of the technique in order to prevent the opponent from attacking with coordination and control (11). Due to the fact that proper use of muscles plays an important role in the performance of Mawashi-Geri technique in Karate (4), the stabilizing muscles are of importance during knee extension, especially the medial muscle of the quadriceps (rectus femoris muscle) (5,12). Studies by Lotfian et al suggested that EMG activity was significantly higher in the tensor fasciae latae, sartorius and hamstring muscles in Mawashi-Geri technique (13).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Taekwondo fighters require sufficient postural stability to better maintain tactical superiority over an opponent [1]. Up-to-date research is focused towards investigating postural balance during bipedal and unipedal stances while facing forward [2].…”
Section: Introductionmentioning
confidence: 99%